Case report: spontaneous (true) aneurysm of the superficial temporal artery - Joalsen, Ivan; Sianturi, G; Niasari, M (Folia Medica Indonesiana, 2017)
Spontaneous aneurysms of the superficial temporal artery (STA) are rare. Although STA aneurysms have a relatively benign course, when compared with aneurysms of larger caliber arteries, they may occasionally lead to severe hemorrhage and be associated with a multitude of bothersome symptoms. The objective of this study was to report a case of 72-year old male presented with spontaneous STA aneurysm. A 72 years old male presented with a lump on his right temporal side without any previous history of trauma and there was history of long standing hypertension. The lump had first been noticed 2 years before and it had been gradually increasing in size especially within last 6 months. On physical examination there was a pulsatile mass around 2 cm in diameter just above right ear. There was no thrill and bruit. CT angiography showed findings compatible with a STA aneurysm. The patient underwent proximal and distal ligation of the superficial temporal artery and excision of the aneurysm. Histopathological examination confirmed a true aneurysm of STA. The post operative period was uneventful. In conclusion, spontaneous STA aneurysm was best managed by surgical procedure. It consists of ligation and excision. It is simple, safe, and avoids recurrence.